PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEB GOOGLE SITES PADA PEMBELAJARAN BAHASA INDONESIA KELAS IV SDN 07 SITIUNG - Amar Salahuddin; M. Anggrayni; Kenny Puspita Dewi (STKIP Subang, 2023)
This research is motivated by the use of Google Sites web-based learning media which is not optimally taught to students. This study aims to produce Google Sites Web-Based learning media in Class IV Indonesian Language Learning at SDN 07 Sitiung that is valid, practical and effective. This type of research is research and development (Research and Development). The development model used is the ADDIE model. This research was conducted at SDN 07 Sitiung. The research subjects were fourth grade elementary school students. Validity test research data obtained through expert validation sheets. Practicality data was collected through teacher response questionnaires and student response questionnaires. Effectiveness data was tested through test questions. The collected data were analyzed based on the research results.Based on the results of the 5 validity test from 4 expert validators obtained a content validation score of 83%, a language validation score of 90%, a graphic validation score of 84%, a question validation score of 86% and an RPP validation score of 88%. So that the average percentage data obtained is 86.2% with a very valid category. The results of the teacher's response practicality test obtained 86% results, while the results of the student response questionnaire obtained 79.25% results in the very practical category. The results of the effectiveness test get an average percentage of 78.25% in the very effective category. Based on these results, it can be concluded that the google sites web-based learning media for learning Indonesian at SDN 07 Sitiung which was developed can be declared valid, practical and effective.